Optimisation of Ultrasound-Assisted Extraction Conditions for Phenolic Content and Antioxidant Capacity from Euphorbia tirucalli Using Response Surface Methodology - Quan V. Vuong; Chloe D. Goldsmith; Trung Thanh Dang; Van Tang Nguyen; Deep Jyoti Bhuyan; Elham Sadeqzadeh; Christopher J. Scarlett; Michael C. Bowyer (MDPI AG, 2014)
Euphorbia tirucalli (E. tirucalli) is now widely distributed around the world and is well known as a source of traditional medicine in many countries. This study aimed to utilise response surface methodology (RSM) to optimise ultrasonic-assisted extraction (UAE) conditions for total phenolic compounds (TPC) and antioxidant capacity from E. tirucalli leaf. The results showed that ultrasonic temperature, time and power effected TPC and antioxidant capacity; however, the effects varied. Ultrasonic power had the strongest influence on TPC; whereas ultrasonic temperature had the greatest impact on antioxidant capacity. Ultrasonic time had the least impact on both TPC and antioxidant capacity. The optimum UAE conditions were determined to be 50 °C, 90 min. and 200 W. Under these conditions, the E. tirucalli leaf extract yielded 2.93 mg GAE/g FW of TPC and exhibited potent antioxidant capacity. These conditions can be utilised for further isolation and purification of phenolic compounds from E. tirucalli leaf.